Correlation between Extracellular Matrix Metalloproteinase Inducer in Peripheral Blood and Serum MMPs in patients with Acute Coronary Syndrome: Correlation between EMMPRIN and MMPs with ACS - Wang, Wei (Cellular and Molecular Biology, 2022)
This research aimed to investigate the expression level of Extracellular matrix metalloproteinase inducer (EMMPRIN) in peripheral blood and matrix metalloproteinases (MMPs) in the serum of patients with acute coronary syndrome, and to clarify the relationship between them, so as to analyze the pathogenesis of the coronary syndrome. For this purpose, 232 patients (patient group) with the acute coronary syndrome (ACS) diagnosed in the cardiology department of our hospital from May 2020 to March 2021 were collected, and the coronary angiography results of 76 healthy people (healthy group) were collected at the same time, and the index differences between the two groups were compared. First, compare the EMMPRIN expression level of the two groups of subjects, including EMMPRIN on the surface of platelets and monocytes. Second, analyze the difference in MMPs expression level between the two groups, and compare the difference of EMMPRIN and MMPs expression levels in different types of patients according to the disease type. Finally, correlation analysis was used to evaluate the correlation between EMMPRIN and MMPs expression levels in patients, and the ability of mutual regulation between them was analyzed. Results showed that The expression levels of EMMPRIN and MMPs in patients were significantly different from those in healthy patients (P<0.05), and the expression levels of EMMPRIN and MMPs in different types of patients were significantly different (P<0.05). The distribution of coronary plaque in different types of patients was significantly different, and the expression levels of EMMPRIN and MMPs in patients with a different coronary plaque were significantly different (P<0.05). There was a positive correlation between EMMPRIN on the platelet surface and MMPs expression in serum, and a positive correlation between EMMPRIN on the monocyte surface and MMPs expression in serum. In conclusion, the peripheral blood EMMPRIN and serum MMPs in patients with acute coronary syndrome were significantly higher than those in healthy people, and the expression of EMMPRIN in patients with the acute coronary syndrome was positively correlated with serum MMPs.